The impact of farm household tourism operations on poverty reduction and conservation under the control policies of China’s protected areas - He, Dan; Wang, Jingwen; Liu, Xiang; Shi, Xiaoliang; Xu, Zhe; Wang, Yang; Qiu, Yingying; Chen, Ke (Frontiers in Environmental Science, 2023)
Against the global trend of increasing multiple participants involvement in protected areas management, the Chinese government has implemented a series of stricter policies since 2015. Tourism is an important alternative livelihood for farmers near protected areas. Based on survey data from 1028 households in six protected areas, this study uses the propensity score matching (PSM) method to empirically examine the change effects of poverty reduction and conservation of farmers engaged in tourism under the influence of protected areas tourism management policies. The PSM method reduces sample self-selection bias and improves the accuracy of research conclusions. The findings reveal that irrespective of whether the areas are subjected to regulatory policies or not, tourism operations are significantly and inversely correlated with households' multidimensional poverty index, and are notably positively correlated with their comprehensive conservation index. Consequently, tourism operations exhibit substantial poverty alleviation and protective effects. However, the current suite of protected areas control policies has curtailed the sustainable growth of tourism within these areas, resulting in a 9.64% decrease in poverty alleviation effects and a 10.33% decrease in protective effects derived from tourism operations. Despite their restrictive impacts on tourism, these policies have yielded some positive outcomes, fostering social equity within protected areas and catalyzing the transition from traditional livelihoods. Drawing upon these empirical findings, this study proposes recommendations and directions for fine-tuning China's existing regulatory policies pertaining to tourism in protected areas.